Reflecting on Maltese school‐based counselling practices: An autoethnographic collaborative writing project. Issue 1 (9th September 2019) - Falzon, Ruth; Galea, Carmen; Galea, Rita; Galea, Silvia; Muscat, Maud
Abstract: Maltese counsellors working in schools are, at times, just making ends meet due to lack of human resources and work schedules. 'Why do our students/children have to repeat the same story to so many professionals?' teachers/parents angrily query. This autoethnographic study voices our professional experiences as authors and participants. This empowers us to be advocates for our young clients. Collaborative autoethnography (CAE) methodology best fits our research question as we 'seek to discover and systemically analyze (graphy) personal experience (auto)…understand cultural experience (ethno)' (Ellis, Adams, & Brochner, 2011, p. 273). Our writing and reflections conclude that best practices include counsellors who work, at least, in pairs within transdisciplinary teams at one school for cycles of five years, with clarity of roles across professionals.